Preparation method and application of efficient silicon-carbon composite graphite material
The silicon-carbon composite graphite material designed through porous treatment and gradient coating solves the volume expansion and interface stability of the silicon-based negative electrode material, improves the cycle stability and high-rate performance of lithium-ion batteries, and is suitable for electric vehicles, grid energy storage systems and portable electronic devices.
Patent Information
- Application Number
- CN202510553780.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-29
- Publication Date
- 2025-08-01
AI Technical Summary
The existing silicon-based anode materials in lithium-ion batteries have poor cycle stability and high-rate performance due to volume expansion, insufficient interface stability and electrical conductivity, which limits their application in the fields of high-energy density lithium batteries and new energy vehicles.
Through the surface treatment of porous silicon particles, the construction of carbon coating and flexible protective layer, the composite of silicon particles and graphite and the optimization of multifunctional coating, high-efficiency silicon-carbon composite graphite materials, including aminoation treatment, ultra-thin SiO2 coating, double-layer carbon coating and gradient coating design.
It significantly improves the structural stability and interface chemical stability of silicon particles, enhances the conductive network, improves the high-rate charging and discharging performance and interface reaction stability, and extends the battery life. It is suitable for electric vehicles, grid energy storage systems and portable electronic devices for lithium-ion batteries.
Smart Images

Figure CN120413588A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of anode materials for lithium-ion batteries, and specifically to a preparation method and application of an efficient silicon-carbon composite graphite material. Background Art
[0002] As the core technology of energy storage devices, the performance of lithium-ion batteries directly determines the energy density, cycle life, and charge-discharge efficiency of battery applications. However, the specific capacity of traditional graphite anode materials (372 mAh / g) has approached the theoretical limit, making it difficult to meet the requirements of high-energy-density lithium batteries. For this reason, silicon-based anode materials have become the research focus of next-generation lithium-ion battery anode materials due to their ultra-high theoretical specific capacity (4200 mAh / g).
[0003] Although silicon materials have significant theoretical advantages, their practical applications face many challenges. During charge and discharge, silicon undergoes a volume expansion of up to 300%, and this drastic volume change can lead to particle rupture, causing mechanical failure of active materials and damage to the conductive network. At the same time, a severe side reaction occurs between silicon and the electrolyte, and the repeatedly ruptured and rebuilt solid electrolyte interface film (SEI film) further consumes electrolyte and lithium-ion resources, increases the interface impedance, and significantly reduces the cycle stability of the battery. In addition, the low conductivity of silicon materials also limits their application performance under high-rate charge and discharge conditions, and the chemical instability at high temperatures further restricts the popularization of silicon-based anode materials in fields such as new energy vehicles.
[0004] Existing research attempts to improve the performance of silicon-based anodes through different technical means. For example, carbon coating on the surface of silicon particles is used to enhance conductivity, nanosizing and porous strategies are adopted to alleviate volume expansion, and silicon is compounded with graphite to improve structural stability. However, these technical methods often fail to systematically solve the multiple problems of silicon-based materials. For example, single-layer carbon coating is prone to peeling during long-term cycling. Although nanosizing and porous treatment can improve stability, the reduction of tap density will affect the energy density of the material. In addition, there is still a large room for optimization in the interface stability and conductive network of composite material design under actual working conditions.
[0005] Therefore, to break through the technical bottleneck of silicon-based anode materials, it is necessary to start from multiple dimensions such as particle structure stability, interface chemical stability, and conductive network optimization. The present invention proposes a preparation method and application of an efficient silicon-carbon composite graphite material. Summary of the Invention
[0006] Aiming at the deficiencies of the existing technology, the present invention provides a preparation method and application of an efficient silicon-carbon composite graphite material, which solves the problems of silicon-based anode materials in terms of volume expansion, interface stability, and insufficient conductivity.
[0007] To achieve the above object, the present invention is realized through the following technical solutions: A preparation method of an efficient silicon-carbon composite graphite material, comprising the following steps: S1. Porous formation and size regulation of silicon particles: The industrial-grade silicon powder is ball-milled to obtain nano-silicon particles, and a porous structure is formed by acid etching; S2. Functionalized surface treatment and interface optimization: Functionalized molecules are introduced onto the surface of the silicon particles and a ultrathin SiO2 protective film is coated; S3. Carbon coating and flexible protective layer construction: The porous silicon particles are pyrolyzed using a carbon source to form a uniform carbon coating layer, and a flexible dynamic protective layer is introduced onto its surface; S4. Composite of silicon particles and graphite: The carbon-coated silicon particles and graphite powder are mixed in proportion, and gradient-structured silicon-carbon composite particles are prepared by spray drying; S5. Multifunctional coating optimization: A graphene layer and a metal oxide layer are sequentially coated onto the surface of the composite particles.
[0008] Preferably, the porous formation and size regulation of the silicon particles in step S1 specifically comprises the following steps: S1.1. Particle size regulation: The industrial-grade silicon powder is processed by a ball-milling process to obtain nano-silicon particles with a particle size of 50-200 nm; S1.2. Particle porous formation: The ball-milled silicon particles are immersed in a mixed acid solution of HF and HNO3 for an etching reaction; S1.3. Drying: The etched silicon particles are washed with deionized water until neutral and vacuum-dried at 60°C - 100°C for 8 - 12 h.
[0009] Preferably, the range of the ball-milling process parameters in step S1.1 is as follows: The ball-milling speed is 400 - 600 rpm, the ball-milling time is 4 - 8 h, and the mass ratio of the silicon powder to the ball-milling medium is 1:4 to 1:6; the range of the etching reaction parameters in step S1.2 is as follows: The volume ratio of the acid solution is 1:1 to 1:3, the reaction time is 1 - 3 h, and the temperature is 20°C - 30°C.
[0010] Preferably, the functionalized surface treatment and interface optimization in step S2 specifically comprises the following steps: S2.1. Amination surface treatment: The porous silicon particles are dispersed in a 1 - 2 M amino-silane solution; S2.2. Introduction of ultrathin SiO2 coating: Tetraethoxysilane solution is coated by a sol-gel method.
[0011] Preferably, the range of the parameters for coating the tetraethoxysilane solution by the sol-gel method in step S2.2 is as follows: The concentration of the TEOS solution is 5-15 wt.%, the temperature is 20-50 °C, and after coating, it is annealed at 250-350 °C for 2-4 hours to form a SiO2 layer with a thickness of 2-5 nm.
[0012] Preferably, the carbon coating and flexible protective layer construction in step S3 specifically include the following steps: S3.1. Carbon coating: Disperse the porous silicon particles in a carbon source solution, where the carbon source is glucose and the solution concentration is 5-15 mg / mL; Use a rotary evaporator to concentrate the solution to a paste; Heat to 700-900 °C at a rate of 5-10 °C / min in an inert atmosphere and hold for 1-3 h to form a carbon coating layer with a thickness of 5-10 nm; S3.2. Flexible protective layer construction: Disperse the carbon-coated silicon particles in a PDMS solution, where the PDMS concentration is 3-10 wt.% and the solvent is anhydrous ethanol; Use the spraying method to coat the particle surface; Heat to 120-180 °C in a nitrogen atmosphere and hold for 15-30 min to form a flexible protective film.
[0013] Preferably, the composite of silicon particles and graphite in step S4 specifically includes the following steps: S4.1. Proportion mixing: Mix the carbon-coated silicon particles, silicon-carbon transition particles, and graphite powder in a mass ratio of 1:2:5; S4.2. Mixing process: Disperse the mixed powder in anhydrous ethanol and use spray drying technology to prepare particles; S4.3. Sintering and curing: Hold in an argon atmosphere at 600-700 °C for 2-4 h.
[0014] Preferably, the mixing process parameters in step S4.2 are as follows: The feeding rate is 8-12 mL / min, the spray gas flow rate is 4-6 L / min, and the drying temperature is 150-200 °C.
[0015] Preferably, the multi-functional coating optimization in step S5 specifically includes the following steps: S5.1. Introduction of graphene coating: Disperse the composite particles in a graphene oxide solution, where the graphene oxide concentration is 1-5 mg / mL; Perform ultrasonic stirring treatment for 1-3 h to form a uniform coating; reduce in an argon atmosphere at 200-250 °C for 2-3 h to form a conductive graphene coating; S5.2. Metal oxide coating: Deposit a TiO2 thin film outside the graphene coating by the sol-gel method; sinter at 400 - 600 °C for 1 - 3 h after coating, and the thickness of the TiO2 coating is 5 - 20 nm.
[0016] A material prepared by a preparation method of a high-efficiency silicon-carbon composite graphite material, which is applied to the negative electrode material of a lithium-ion battery, and the lithium-ion battery is used for electric vehicles, power grid energy storage systems, and portable electronic devices.
[0017] The present invention provides a preparation method and application of a high-efficiency silicon-carbon composite graphite material. It has the following beneficial effects: 1. Through the collaborative design of the flexible protective layer and the gradient coating, the present invention significantly improves the structural stability and interfacial chemical stability of silicon particles during long-term cycling. The flexible protective layer coats the silicon particles with a highly elastic polymer material, which can dynamically adjust the stress on the particle surface during the volume expansion process caused by lithium-ion insertion / extraction, avoiding particle rupture and pulverization. At the same time, the gradient coating combines an inner conductive coating and an outer chemical stable coating, which not only optimizes the electron transport path but also further enhances the chemical inertness of the interface, reducing the occurrence of side reactions. This dual design effectively overcomes the problem of rapid capacity decay caused by the volume effect of silicon-based negative electrode materials and significantly extends the service life of the battery.
[0018] 2. Through the synergistic effect of double-layer carbon coating and conductive coating, the present invention constructs an efficient conductive network, thereby significantly improving the charge and discharge performance of the silicon-carbon composite material under high-rate conditions. The double-layer carbon coating consists of an inner dense carbon layer and an outer porous carbon layer. The inner dense carbon layer improves the mechanical strength and electron conductivity of the material, while the outer porous carbon layer provides more interface contact points, accelerating the charge transfer and lithium-ion diffusion rate. In addition, an external conductive coating such as graphene further optimizes the overall conductive performance, providing a fast electron and ion transport channel for high-rate discharge. This structural design meets the requirements of fast charging and high-rate applications of lithium batteries and is an important technological breakthrough in improving the conductivity and rate performance of materials.
[0019] 3. Through functional surface treatment and gradient coating technology, the present invention solves the problem of unstable interfacial reaction between silicon particles and electrolyte. The functional treatment introduces a lithiumophilic interfacial layer on the surface of silicon particles through amino silane modification, significantly reducing the initial irreversible capacity loss and inhibiting the decomposition reaction of the electrolyte. At the same time, the gradient coating design uses an inner high-conductive coating and an outer chemically inert coating. The inner layer improves the electron conductivity of the interface, and the outer layer stabilizes the chemical environment of the interface, preventing the repeated formation and rupture of the SEI film. This design fundamentally improves the interfacial stability and cycling performance of silicon-based negative electrode materials and provides a long-term reliable interfacial solution for high-energy-density lithium batteries. Description of the Drawings
[0020] Figure 1 This is the flow chart of the method of the present invention. Specific embodiments
[0021] Next, in conjunction with the accompanying drawings of the present invention specification, the technical solutions in the embodiments of the present invention will be clearly and completely described. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative work fall within the scope of protection of the present invention.
[0022] Please refer to the atta Figure 1 chments. The embodiments of the present invention provide a preparation method of an efficient silicon-carbon composite graphite material, including the following steps: S1. Porous formation and size regulation of silicon particles: The industrial-grade silicon powder is ball-milled to obtain nano-silicon particles, and a porous structure is formed by acid etching. S2. Functionalized surface treatment and interface optimization: Functionalized molecules are introduced on the surface of the silicon particles and a ultrathin SiO2 protective film is coated. S3. Carbon coating and flexible protective layer construction: The porous silicon particles are pyrolyzed with a carbon source to form a uniform carbon coating layer, and a flexible dynamic protective layer is introduced on its surface. S4. Composite of silicon particles and graphite: The carbon-coated silicon particles and graphite powder are mixed in proportion, and gradient structure silicon-carbon composite particles are prepared by spray drying. S5. Multifunctional coating optimization: A graphene layer and a metal oxide layer are sequentially coated on the surface of the composite particles.
[0023] The porous formation and size regulation of silicon particles in step S1 specifically include the following steps: S1.1. Particle size regulation: The industrial-grade silicon powder is processed by a ball-milling process to obtain nano-silicon particles with a particle size of 50-200 nm. S1.2. Particle porous formation: The ball-milled silicon particles are immersed in a mixed acid solution of HF and HNO3 for etching reaction. S1.3. Drying: The etched silicon particles are washed with deionized water until neutral, and vacuum dried at 60°C - 100°C for 8 - 12 h.
[0024] The range of ball-milling process parameters in step S1.1 is as follows: The ball-milling speed is 400 - 600 rpm, the ball-milling time is 4 - 8 h, and the mass ratio of silicon powder to ball-milling medium is 1:4 to 1:6; the range of etching reaction parameters in step S1.2 is as follows: The volume ratio of the acid solution is 1:1 to 1:3, the reaction time is 1 - 3 h, and the temperature is 20°C - 30°C.
[0025] The functionalized surface treatment and interface optimization in step S2 specifically include the following steps: S2.1. Amination surface treatment: Dispersing porous silicon particles in a 1 - 2M amino - silane solution; S2.2. Introduction of ultrathin SiO2 coating: Coating tetraethyl orthosilicate solution by sol - gel method.
[0026] The parameter range of coating tetraethyl orthosilicate solution by sol - gel method in step S2.2 is as follows: The concentration of TEOS solution is 5 - 15wt.%, the temperature is 20 - 50°C, annealed at 250 - 350°C for 2 - 4 hours after coating to form a SiO2 layer with a thickness of 2 - 5nm.
[0027] The carbon coating and flexible protective layer construction in step S3 specifically include the following steps: S3.1. Carbon coating: Disperse porous silicon particles in a carbon source solution, the carbon source is glucose, and the solution concentration is 5 - 15mg / mL; Use a rotary evaporator to concentrate the solution to a paste; Heat to 700 - 900°C at a rate of 5 - 10°C / min in an inert atmosphere and hold for 1 - 3h to form a carbon coating layer with a thickness of 5 - 10nm; S3.2. Flexible protective layer construction: Disperse the carbon - coated silicon particles in a PDMS solution, the PDMS concentration is 3 - 10wt.%, and the solvent is absolute ethanol; Use the spraying method to coat the particle surface; Heat to 120 - 180°C in a nitrogen atmosphere and hold for 15 - 30min to form a flexible protective film.
[0028] The composite of silicon particles and graphite in step S4 specifically includes the following steps: S4.1. Proportion mixing: Mix the carbon - coated silicon particles, silicon - carbon transition particles and graphite powder in a mass ratio of 1:2:5; S4.2. Mixing process: Disperse the mixed powder in absolute ethanol and prepare particles by spray - drying technology; S4.3. Sintering and curing: Keep warm for 2 - 4h in an argon atmosphere at 600 - 700°C.
[0029] The parameter range of the mixing process in step S4.2 is as follows: The feeding rate is 8 - 12mL / min, the spray gas flow rate is 4 - 6L / min, and the drying temperature is 150 - 200°C.
[0030] The optimization of the multi - functional coating in step S5 specifically includes the following steps: S5.1. Introduction of graphene coating: Disperse the composite particles in the graphene oxide solution with a graphene oxide concentration of 1 - 5 mg / mL; Perform ultrasonic stirring treatment for 1 - 3 h to form a uniform coating; reduce it in an argon atmosphere at 200 - 250 °C for 2 - 3 h to form a conductive graphene coating; S5.2. Metal oxide coating: Deposit a TiO2 thin film on the graphene coating by the sol - gel method; sinter it at 400 - 600 °C for 1 - 3 h after coating, and the thickness of the TiO2 coating is 5 - 20 nm.
[0031] A material prepared by the preparation method of a high - efficiency silicon - carbon composite graphite material is applied to the anode material of a lithium - ion battery, and the lithium - ion battery is used in electric vehicles, power grid energy storage systems, and portable electronic devices.
[0032] Example 1: Specific implementation steps: Porous formation and size regulation of silicon particles: Ball - milling process: Add industrial - grade silicon powder to a ball mill at a mass ratio of silicon powder: ball - milling medium = 1:5, with a rotation speed of 500 rpm and a ball - milling time of 6 hours to obtain nano - silicon particles with a particle size of 100 nm.
[0033] Etching reaction: Immerse the nano - silicon particles in a mixed acid solution of HF and HNO3 (volume ratio 1:2), with a reaction time of 2 hours and a temperature of 25 °C to form a porous structure.
[0034] Drying: Wash the etched silicon particles with deionized water until neutral, and dry them in a vacuum at 80 °C for 10 hours.
[0035] Functionalized surface treatment and interface optimization: Amination surface treatment: Disperse the porous silicon particles in a 1 M amino - silane solution and stir at 80 °C for 4 hours.
[0036] Ultra - thin SiO2 coating: Disperse the aminated particles in a 10 wt.% tetraethoxysilane solution, anneal at 300 °C for 3 hours after coating to form an SiO2 coating with a thickness of 3 nm.
[0037] Carbon coating and flexible protective layer construction: Carbon coating: Disperse the porous silicon particles in a glucose solution (concentration 10 mg / mL), concentrate by rotary evaporation, then heat to 800 °C at a rate of 8 °C / min in an inert atmosphere and hold for 2 hours to form a carbon coating layer with a thickness of 7 nm.
[0038] Flexible protective layer: Disperse the carbon - coated silicon particles in a 5 wt.% PDMS solution, spray - coat, and then heat to 150 °C in a nitrogen atmosphere and hold for 20 minutes.
[0039] Composite of silicon particles and graphite: Proportion mixing: Mix carbon-coated silicon particles, silicon-carbon transition particles and graphite powder according to the mass ratio of 1:2:5.
[0040] Spray drying: The feeding rate is 10 mL / min, the spray gas flow rate is 5 L / min, and the drying temperature is 180 °C.
[0041] Sintering and curing: Keep it warm for 3 hours in an argon atmosphere at 650 °C.
[0042] Optimization of multi-functional coating: Graphene coating: Disperse the particles in a 2 mg / mL graphene oxide solution, ultrasonically treat for 2 hours, and reduce in argon at 200 °C for 2 hours.
[0043] TiO2 coating: Deposit a TiO2 thin film by sol-gel method, sinter at 500 °C for 2 hours, and the thickness of the TiO2 coating is 10 nm.
[0044] Summary: Based on the basic technical solution, this example successfully prepared an efficient silicon-carbon composite graphite material through the porousization, functional surface treatment, carbon coating and flexible protective layer construction of silicon particles, the composite of silicon and graphite, and the optimization of the multi-functional coating. This material has excellent electrochemical performance, with a specific capacity of 850 mAh / g. After 1000 cycles at a rate of 0.5C, the capacity retention rate reaches 90%. This example provides a basic reference for subsequent optimization.
[0045] Example 2: Specific implementation steps: On the basis of Example 1, introduce particle size distribution regulation, and improve the mechanical stability of porous particles by adding micron-sized silicon powder: Particle mixing: Mix micron-sized silicon powder (particle size 3 µm) and nano-sized silicon particles (particle size 100 nm) according to the mass ratio of 2:1, and then carry out ball milling for 6 hours to form a multi-level particle distribution.
[0046] The remaining steps are the same as those in Example 1.
[0047] Summary: On the basis of Example 1, this example improved the mechanical stability of the composite material by optimizing the particle size distribution and adding micron-sized silicon particles (particle size 3 µm) to nano-sized silicon particles. The improved material has excellent high-rate performance, and the specific capacity still remains at 850 mAh / g, but the capacity retention rate at a rate of 2C has increased from 80% in the basic example to 85%. This example verifies the important role of particle size distribution optimization in high-rate stability.
[0048] Example 3: Specific implementation steps: Based on Example 2, the porous etching time was adjusted to optimize the pore structure: Etching reaction: The etching time was extended to 3 hours, the pore size distribution was controlled within 10 - 50 nm, and the porosity was 60%.
[0049] The remaining steps were the same as in Example 2.
[0050] Summary: Based on Example 2, by extending the porous etching time to 3 hours, the porosity and pore size distribution (10 - 50 nm) of the silicon particles were optimized, and the lithium ion transport performance within the particles was improved. The specific capacity of the improved material was further increased to 880 mAh / g, and the capacity retention rate at 0.5C rate remained at 90%. This example shows that optimizing the etching depth is an effective means to increase the specific capacity.
[0051] Example 4: Specific implementation steps: Based on Example 3, a double - layer carbon coating structure was introduced to improve conductivity and stability: First - layer carbon coating: The same as in Example 3.
[0052] Second - layer carbon coating: On the basis of the first - layer carbon coating, the second - layer carbon coating was introduced by CVD method. The deposition temperature was 850 °C, the deposition time was 1 hour, and the thickness of the second - layer carbon was 5 nm.
[0053] The remaining steps were the same as in Example 3.
[0054] Summary: Based on Example 3, a double - layer carbon coating structure was added. By introducing the second - layer carbon coating (thickness 5 nm) prepared by CVD method on the basis of the first - layer carbon coating, the conductivity and structural stability of the composite particles were further improved. The high - rate discharge performance of the improved material was significantly enhanced, and the capacity retention rate at 5C rate reached 80%, verifying the effectiveness of the double - layer carbon coating.
[0055] Example 5: Specific implementation steps: Based on Example 4, the multifunctional coating was optimized to a gradient distribution structure: Adjustment of graphene coating thickness: The coating thickness gradually decreased from the particle core to the outside, decreasing from 5 nm to 2 nm.
[0056] Adjustment of TiO2 coating thickness: The coating thickness gradually decreased from the particle surface to the inside, decreasing from 20 nm to 10 nm.
[0057] The remaining steps were the same as in Example 4.
[0058] Summary: Based on Example 4, this example further improves the interface stability and conductivity by optimizing the coating thickness to a gradient distribution (the graphene coating decreases from 5 nm to 2 nm, and the TiO2 coating decreases from 20 nm to 10 nm). The improved material exhibits excellent comprehensive advantages in terms of electrochemical performance, with a specific capacity reaching 900 mAh / g and a capacity retention rate of 90% after 1500 cycles at a 2C rate. This example provides a comprehensive technical reference for the final optimization.
[0059] Summary and conclusion: Through the gradual optimization from Example 1 to Example 5, this technical solution has achieved a comprehensive improvement of the high-performance silicon-carbon composite graphite material: Example 1 provides the basic preparation process, ensuring a high specific capacity (850 mAh / g) and a long cycle life (capacity retention rate of 90%).
[0060] Example 2 significantly improves the mechanical stability and high-rate performance of the material (the capacity retention rate at a 2C rate is increased to 85%) through particle size grading optimization.
[0061] Example 3 optimizes the porosity and lithium-ion transport performance by adjusting the depth of porous etching, achieving a further increase in specific capacity (880 mAh / g).
[0062] Example 4 introduces a double-layer carbon coating structure, enhancing the conductive network and the stability of the particle structure, and showing outstanding high-rate performance (capacity retention rate of 80% at a 5C rate).
[0063] Example 5 significantly improves the interface stability and comprehensive electrochemical performance through the optimization of the coating gradient distribution, with a specific capacity reaching 900 mAh / g and a capacity retention rate of 90% after 1500 cycles at a 2C rate.
[0064] Comparative experiment: Experimental purpose Through the comparative tests of the materials of the five examples of the present invention (E1-E5) and the materials of the prior art (C1-C3), experiments are carried out from multiple dimensions such as specific capacity, first Coulomb efficiency, long-cycle stability, high-rate performance, thermal stability, and interfacial electrochemical performance to verify the significant advantages of the technical solution of the present invention, and systematically analyze the contributions of each optimization step (such as particle size grading, porousization, double-layer carbon coating, flexible protective layer, and coating gradient design) to the performance.
[0065] Experimental design and variables: Experimental groups: Materials of the examples of the present invention (E1-E5): E1: Basic example material.
[0066] E2: Material with optimized particle size grading.
[0067] E3: Porous depth optimization material.
[0068] E4: Double-layer carbon-coated optimization material.
[0069] E5: Coating gradient optimization material.
[0070] Control group materials (C1-C3): C1: Silicon particles without any treatment.
[0071] C2: Silicon-carbon composite material with single-layer carbon coating in the prior art.
[0072] C3: Silicon-carbon material that has been compounded with single-layer carbon coating and graphite but without functionalization treatment or coating optimization.
[0073] 2. Experimental test content 2.1 Electrochemical performance test Specific capacity and first Coulombic efficiency: Purpose: To test the initial capacity and first Coulombic efficiency, and verify the lithium-ion storage efficiency of each material in the initial cycle.
[0074] Test conditions: Constant current charge and discharge are carried out at a rate of 0.1C.
[0075] Monitored data: First charge and discharge capacity, first Coulombic efficiency.
[0076] Long cycle stability test: Purpose: To verify the capacity retention ability of the material during long-term cycling, and evaluate the effects of porous structure and protective layer on cycle stability.
[0077] Test conditions: Cycle 3000 times at a rate of 0.5C, and record the capacity change every 100 times.
[0078] Monitored data: Capacity retention rate and capacity decay rate during cycling.
[0079] Rate performance test: Purpose: To evaluate the fast charge and discharge ability of the material at different rates, and analyze the improvement of the coating and conductive network on the high-rate performance.
[0080] Test conditions: Test the capacity at rates of 0.1C, 0.5C, 1C, 2C, 5C, 10C, and 20C in sequence.
[0081] Monitored data: Discharge capacity and rate retention rate at different rates.
[0082] Analysis of voltage platform pressure difference: Purpose: To evaluate the interfacial stability of different materials during long-term cycling through the voltage platform pressure difference.
[0083] Test conditions: Record the charge-discharge curves and analyze the differences in voltage platforms before and after cycling.
[0084] Monitored data: The variation of voltage platform differences with the number of cycles.
[0085] 2.2 Thermal stability test Initial temperature of thermal decomposition and weight loss rate: Purpose: Test the initial temperature of thermal decomposition and the weight loss characteristics during decomposition of different materials, and evaluate the thermal stability of the coating and protective layer.
[0086] Test conditions: Use TGA and DSC tests, heating rate of 10 °C / min, temperature range of 25 - 600 °C.
[0087] Monitored data: Initial temperature of thermal decomposition, decomposition weight loss rate and heat flow curve.
[0088] Thermal cycling stability: Purpose: Test the structural stability of the material during repeated high-temperature - normal-temperature changes.
[0089] Test conditions: Set a cyclic environment of 100 °C - 25 °C, and test the change in specific capacity of the material after 20 thermal cycles.
[0090] Monitored data: Capacity retention rate after thermal cycling.
[0091] 2.3 Interfacial electrochemical performance test Interfacial impedance test (EIS): Purpose: Test the initial interfacial impedance and the change in interfacial impedance after cycling, and evaluate the influence of the coating and functionalization treatment on interfacial stability.
[0092] Test conditions: Frequency range from 10 6 Hz to 0.1 Hz.
[0093] Monitored data: Initial interfacial impedance, impedance change after 200 cycles.
[0094] Dynamic SEI film analysis: Purpose: Analyze the composition and distribution of the SEI film formed during cycling of the material, and explore the stability of interfacial chemical reactions.
[0095] Test conditions: Use XPS to characterize the chemical composition of the SEI film before and after cycling.
[0096] Monitored data: Proportion changes of the contents of LiF, Li2CO3 and organic substances in the SEI film.
[0097] 2.4 Microstructural characterization Test for the stability of particle morphology: Objective: To test the change in particle morphology before and after cycling of the material and verify the mechanical stability of the particles.
[0098] Test conditions: Use SEM and TEM to observe the surface morphology and internal structure of the particles.
[0099] Monitoring data: Particle morphology retention rate.
[0100] Coating integrity and distribution: Objective: To analyze the uniformity of the coating and its integrity after cycling.
[0101] Test conditions: Use EDS and AFM to detect the coating distribution and thickness on the particle surface.
[0102] Monitoring data: Changes in coating thickness and distribution.
[0103] Experimental procedure: 1. Electrode preparation and battery assembly Material preparation: Mix materials E1 - E5 and C1 - C3 with PVDF at a mass ratio of 8:2 respectively, add NMP solvent, and stir for 6 hours to make a slurry.
[0104] Coating and drying: Coat the slurry on copper foil, pre - dry at 80 °C for 1 hour, then cut into electrode sheets with a diameter of 14 mm, and vacuum - dry at 120 °C for 12 hours.
[0105] Button cell assembly: In a drying chamber, use a lithium sheet as the counter electrode to assemble a CR2032 button cell, add 1M LiPF6 electrolyte, and let it stand for 12 hours before testing.
[0106] 2. Testing and monitoring Conduct various tests according to the above experimental design, record data and analyze.
[0107] Experimental results: 1. Specific capacity and initial Coulombic efficiency Analysis: The unprocessed silicon particles (C1) have a specific capacity as high as 1200 mAh / g, but the initial Coulombic efficiency is only 55%. Due to the serious reaction between the silicon surface and the electrolyte, a large amount of irreversible capacity loss occurs.
[0108] Existing technologies (C2, C3) improve the initial Coulombic efficiency (73% - 80%) through single - layer carbon coating and graphite composite, but still cannot avoid the volume effect of silicon and the instability of the SEI film.
[0109] The materials of the present invention (E1 - E5) have successfully increased the initial Coulombic efficiency to 85% - 90% through functionalized surface treatment, double - layer carbon coating, flexible protective layer and coating optimization, significantly reducing the irreversible capacity loss, which proves the key role of the optimized design in interface stability.
[0110] Summary: The functionalized surface treatment effectively passivates the surface of active silicon, reducing the initial lithium consumption; the flexible protective layer alleviates the interface damage caused by the volume expansion of silicon, which is the key to the improvement of the initial Coulombic efficiency.
[0111] 2. Long - cycle stability Analysis: The capacity retention rate of the untreated silicon particles (C1) is only 10%, showing extremely poor cycle stability, indicating that the pulverization of particles caused by volume expansion is the main problem of silicon materials.
[0112] The existing technologies (C2, C3) have some improvement in cycle performance (55% - 70%), but due to the ineffective alleviation of the expansion problem by single - layer carbon coating and simple graphite composite, the capacity retention rate is still limited.
[0113] The materials of the present invention (E1 - E5) have a capacity retention rate of 85% - 95% after 3000 cycles. Especially for the E5 material, with the flexible protective layer and gradient coating design, the cycle stability reaches 95%, significantly superior to C3.
[0114] Summary: The double - layer carbon coating and the flexible protective layer provide an effective buffering effect, protecting the structural integrity of silicon particles; the gradient coating further improves the chemical and mechanical stability of the interface, greatly enhancing the cycle performance.
[0115] 3. Rate performance Analysis: The rate performance of the untreated silicon particles (C1) is extremely poor, only maintaining a capacity of 20 mAh / g at a rate of 5C, and almost failing at rates of 10C and 20C, indicating poor conductivity and interface stability.
[0116] The existing technologies (C2, C3) have improved rate performance, with capacities reaching 200 - 300 mAh / g and 100 - 150 mAh / g at 5C and 10C respectively, but still showing significant attenuation at a rate of 20C.
[0117] The materials of the present invention (E1 - E5) show excellent performance at high rates. Especially for the E5 material, it can still maintain a capacity of 450 mAh / g at a rate of 20C, indicating that the double - layer carbon coating and coating optimization significantly improve the integrity of the conductive network and interface performance.
[0118] Summary: Double - layer carbon coating and conductive coating optimization have significantly improved the electron transport performance and interfacial reaction rate at high rates; the gradient coating design further enhances the stability of high - rate charge and discharge.
[0119] 4. Thermal stability Analysis: The thermal decomposition onset temperature of the untreated silicon particles (C1) is only 150 °C, showing extremely poor thermal stability.
[0120] Existing technologies (C2, C3) increase the thermal decomposition onset temperature to 200 - 220 °C through carbon coating, but due to insufficient coating and protective layer design, the improvement in thermal stability is limited.
[0121] The thermal decomposition onset temperature of the materials of the present invention (E1 - E5) is significantly increased to 250 - 300 °C, among which the E5 material reaches 300 °C, the thermal weight loss rate is only 10%, and the capacity retention rate after thermal cycling is as high as 95%.
[0122] Summary: The synergistic effect of coating optimization and flexible protective layer has significantly improved the thermal stability and thermal decomposition resistance of the materials.
[0123] 5. Analysis of interfacial electrochemical performance Data analysis: The interfacial impedance of the material E5 of the present invention is the lowest, initially only 30 Ω, and only increases to 35 Ω after 200 cycles, far better than C2 and C3.
[0124] Functionalization treatment and coating optimization effectively reduce the interfacial electrochemical reaction impedance and improve the interfacial stability.
[0125] Summary: Functionalization treatment and coating optimization significantly improve the interfacial reaction conditions and SEI film stability, ensuring long - cycle performance.
[0126] Summary summary: Specific capacity and first - cycle Coulombic efficiency: Through functionalization treatment and flexible protective layer design, the first - cycle Coulombic efficiency of the materials of the present invention (E5) reaches 90%, significantly reducing the initial irreversible loss of lithium ions.
[0127] Long - cycle stability: The capacity retention rate of the E5 material is 95% after 3000 cycles, significantly better than the existing technology (70% of C3), proving the significant role of the flexible protective layer and gradient coating in suppressing the volume expansion of silicon particles.
[0128] Rate performance: The capacity of E5 material remains as high as 450 mAh / g at the 20C rate, which is 4.5 times that of C3, indicating that the double-layer carbon coating and conductive coating have greatly improved the high-rate performance.
[0129] Thermal stability: The initial temperature of thermal decomposition of E5 material reaches 300°C, and the thermal weight loss rate is only 10%, showing excellent high-temperature stability and being suitable for applications in high-temperature environments.
[0130] Interface performance and microstructure stability: The interface impedance of E5 material is the lowest and changes minimally, and the particle morphology retention rate is as high as 98%, fully verifying the effectiveness of the coating and protective layer in improving interface stability and particle integrity.
[0131] Conclusion: Through systematic optimization, the technical solution of the present invention has significantly improved the electrochemical performance, thermal stability, and interface stability of the material, showing extremely high innovation and broad application potential, and providing a comprehensive solution for high-performance anode materials of lithium-ion batteries.
[0132] Although the embodiments of the present invention have been shown and described, it will be understood by those of ordinary skill in the art that various changes, modifications, substitutions, and variations can be made to these embodiments without departing from the principles and spirit of the present invention, and the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A preparation method of an efficient silicon-carbon composite graphite material, characterized in that, It includes the following steps: S1. Porous formation and size regulation of silicon particles: Industrial-grade silicon powder is ball-milled to obtain nano-silicon particles, and a porous structure is formed by acid etching. S2. Functionalized surface treatment and interface optimization: Functionalized molecules are introduced onto the surface of silicon particles, and a ultrathin SiO2 protective film is coated. S3. Carbon coating and flexible protective layer construction: The porous silicon particles are pyrolyzed with a carbon source to form a uniform carbon coating layer, and a flexible dynamic protective layer is introduced on its surface. S4. Composite of silicon particles and graphite: The carbon-coated silicon particles and graphite powder are mixed in proportion, and gradient-structured silicon-carbon composite particles are prepared by spray drying. S5. Optimization of multi-functional coating: A graphene layer and a metal oxide layer are successively coated on the surface of the composite particles.
2. The preparation method of an efficient silicon-carbon composite graphite material according to claim 1, characterized in that, The porous formation and size regulation of silicon particles in step S1 specifically include the following steps: S1.
1. Particle size regulation: Industrial-grade silicon powder is processed by a ball-milling process to obtain nano-silicon particles with a particle size of 50 - 200 nm. S1.
2. Particle porous formation: The ball-milled silicon particles are immersed in a mixed acid solution of HF and HNO3 for etching reaction. S1.
3. Drying: The etched silicon particles are washed with deionized water until neutral, and vacuum-dried at 60℃ - 100℃ for 8 - 12 h.
3. The preparation method of an efficient silicon-carbon composite graphite material according to claim 2, characterized in that, The ranges of ball-milling process parameters in step S1.1 are as follows: The ball-milling speed is 400 - 600 rpm, the ball-milling time is 4 - 8 h, and the mass ratio of silicon powder to ball-milling medium is 1:4 to 1:
6. The ranges of etching reaction parameters in step S1.2 are as follows: The volume ratio of the acid solution is 1:1 to 1:3, the reaction time is 1 - 3 h, and the temperature is 20℃ - 30℃.
4. The preparation method of an efficient silicon-carbon composite graphite material according to claim 1, characterized in that, The functionalized surface treatment and interface optimization in step S2 specifically include the following steps: S2.
1. Amination surface treatment: The porous silicon particles are dispersed in a 1 - 2M amino-silane solution. S2.
2. Introduction of ultrathin SiO2 coating: Tetraethoxysilane solution is coated by the sol-gel method.
5. The preparation method of an efficient silicon-carbon composite graphite material according to claim 4, characterized in that, The ranges of parameters for coating tetraethoxysilane solution by the sol-gel method in step S2.2 are as follows: The concentration of TEOS solution is 5 - 15 wt.%, the temperature is 20 - 50℃, and after coating, it is annealed at 250 - 350℃ for 2 - 4 hours to form a SiO2 layer with a thickness of 2 - 5 nm.
6. The preparation method of an efficient silicon-carbon composite graphite material according to claim 1, wherein The carbon coating and flexible protective layer construction in step S3 specifically include the following steps: S3.
1. Carbon coating: The porous silicon particles are dispersed in a carbon source solution, the carbon source is glucose, and the solution concentration is 5 - 15 mg / mL. The solution is concentrated to a paste using a rotary evaporator. It is heated to 700 - 900℃ at a rate of 5 - 10℃ / min in an inert atmosphere and held for 1 - 3 h to form a carbon coating layer with a thickness of 5 - 10 nm. S3.
2. Flexible protective layer construction: The carbon-coated silicon particles are dispersed in a PDMS solution, the PDMS concentration is 3 - 10 wt.%, and the solvent is anhydrous ethanol. The particle surface is coated using the spraying method. It is heated to 120 - 180℃ in a nitrogen atmosphere and held for 15 - 30 min to form a flexible protective film.
7. The preparation method of an efficient silicon-carbon composite graphite material according to claim 1, characterized in that, The composite of silicon particles and graphite in step S4 specifically includes the following steps: S4.
1. Proportion mixing: Mix carbon-coated silicon particles, silicon-carbon transition particles and graphite powder in a mass ratio of 1:2:5; S4.
2. Mixing process: Disperse the mixed powder in absolute ethanol and prepare particles by spray drying technology; S4.
3. Sintering and curing: Keep warm for 2 - 4 h in an argon atmosphere at 600 - 700 °C.
8. The preparation method of an efficient silicon-carbon composite graphite material according to claim 7, characterized in that, The mixing process parameter range in step S4.2 is as follows: The feeding rate is 8 - 12 mL / min, the spray gas flow rate is 4 - 6 L / min, and the drying temperature is 150 - 200 °C.
9. The preparation method of an efficient silicon-carbon composite graphite material according to claim 1, characterized in that, The specific optimization of the multifunctional coating in step S5 includes the following steps: S5.
1. Introduction of graphene coating: Disperse the composite particles in a graphene oxide solution with a graphene oxide concentration of 1 - 5 mg / mL; Form a uniform coating by ultrasonic stirring treatment for 1 - 3 h; reduce in an argon atmosphere at 200 - 250 °C for 2 - 3 h to form a conductive graphene coating; S5.
2. Metal oxide coating: Deposit a TiO2 thin film outside the graphene coating by sol-gel method; sinter at 400 - 600 °C for 1 - 3 h after coating, and the thickness of the TiO2 coating is 5 - 20 nm.
10. A material prepared by the preparation method of an efficient silicon-carbon composite graphite material according to any one of claims 1 to 9, which is applied to the anode material of a lithium-ion battery, characterized in that, The lithium-ion battery is used in electric vehicles, grid energy storage systems and portable electronic devices.
Citation Information
Cited By
High-performance silicon carbide rod and preparation method thereof
CN121292979A
High-performance silicon-carbon rod and preparation method thereof
CN121292979B
